2009
DOI: 10.1080/09540120802537849
|View full text |Cite
|
Sign up to set email alerts
|

Case manager-reported utilization of support group, substance use and mental health services among HIV-positive women in New York City

Abstract: A retrospective, longitudinal analysis of case management and medical charts was used to evaluate utilization of support group, mental health, and substance abuse treatment services among HIV-positive women in New York City. Analyses of 4134 case management and supportive service transactions revealed that 70% utilized support groups over the two-year study period. In contrast, only 35% utilized mental health services (therapy) and of those identified as using substances, only 48% utilized substance abuse trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…32 Studies suggest that certain high-risk groups may be especially reluctant to use support resources, including patients who are older, less educated, or those with mental health or substance abuse issues. 32,30 Specifically, the literature suggests difficulty in engaging trauma patients after discharge. 33 Furthermore, subjects were being enrolled into the evaluation group during the program's initial rollout, potentially not allowing enough time for the program to become firmly established.…”
Section: Low Program Usementioning
confidence: 99%
“…32 Studies suggest that certain high-risk groups may be especially reluctant to use support resources, including patients who are older, less educated, or those with mental health or substance abuse issues. 32,30 Specifically, the literature suggests difficulty in engaging trauma patients after discharge. 33 Furthermore, subjects were being enrolled into the evaluation group during the program's initial rollout, potentially not allowing enough time for the program to become firmly established.…”
Section: Low Program Usementioning
confidence: 99%
“…Prior analyses on individual supportive service data of this same sample found differences in use levels by service delivery model, mental illness, and substance use status. 13 However, these findings of the aggregate of supportive service data revealed that the differences in use were more related to the case manager relationship and less about moderating institution-level and person-level factors over the 24-month period.…”
Section: Discussionmentioning
confidence: 88%
“…Lastly, none of the agencies provided standardized mental illness assessments for case managers, although the mental illness prevalence rates (63%) found in our sample are aligned with literature on HIV-positive people. [13][14][15][16][17] …”
Section: Limitationsmentioning
confidence: 98%
“…This is poignantly true for psychosocial resource programs similar to our own. One reason behind this trend is that many high-risk groups, including those with cancer, HIV, and autoimmune diseases, are reluctant to use such services 35–39. For example, a foremost barrier to attending support groups among these populations is a lack of perceived need 38 39.…”
Section: Discussionmentioning
confidence: 99%